PEDAGOGICAL CONDITIONS OF CREATIVITY DEVELOPMENT STUDENT IN THE PRACTICE OF HIGHER EDUCATION - V.A. Fritsyuk (Academy of Cognitive and Natural Sciences, 2007)
The problem of future teacher's creativity of higher pedagogical institutions of education is being researched in the work. The subject, creativity structural components, pedagogical of future teacher's are described.